2017
DOI: 10.18632/oncotarget.21759
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-suppressive function of UNC5D in papillary thyroid cancer

Abstract: BackgroundStudies have shown an association of the UNC5D gene with kidney and bladder cancer and neuroblastoma. We investigated whether UNC5D acts as a tumor suppressor in papillary thyroid carcinoma (PTC).MethodsPrimary PTC tumors and matched normal thyroid tissues were obtained from 112 patients to detect UNC5D mRNA by real-time PCR. Genomic DNA sequencing was performed to detect BRAF mutation in PTC tumors. The association between UNC5D expression and clinicopathological data from PTC patients was reviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Human PTC K1 cells were used in the present study. Though we lately discovered K1 cells were actually cells mixed with GLAG-66 cells, of the thyroid gland papillary carcinoma, it did not affect studying function of the target gene on PTC, which was verified by numerous researches before ( 21 30 ). K1 cells (mixed thyroid gland papillary carcinoma cells) were purchased from ATCC (Guangzhou, China) were cultured in Dulbecco's modified Eagle's medium (DMEM) of 10% fetal bovine serum (FBS; both Gibco; Thermo Fisher Scientific, Inc., Waltham, MA, USA) and 1% penicillin/streptomycin (Invitrogen, Carlsbad, CA, USA) at 37°C with 5% CO 2.…”
Section: Methodsmentioning
confidence: 81%
“…Human PTC K1 cells were used in the present study. Though we lately discovered K1 cells were actually cells mixed with GLAG-66 cells, of the thyroid gland papillary carcinoma, it did not affect studying function of the target gene on PTC, which was verified by numerous researches before ( 21 30 ). K1 cells (mixed thyroid gland papillary carcinoma cells) were purchased from ATCC (Guangzhou, China) were cultured in Dulbecco's modified Eagle's medium (DMEM) of 10% fetal bovine serum (FBS; both Gibco; Thermo Fisher Scientific, Inc., Waltham, MA, USA) and 1% penicillin/streptomycin (Invitrogen, Carlsbad, CA, USA) at 37°C with 5% CO 2.…”
Section: Methodsmentioning
confidence: 81%
“…UNC5D, as a member of the UNC5 family, was identified as a netrin receptor and participated in cell migration and morphogenesis during development [ 27 ]. Previously, UNC5D was found to be a tumor suppressor and frequently downregulated in primary renal cell carcinomas [ 18 ], neuroblastoma [ 28 , 29 ], bladder cancer [ 30 ] and papillary thyroid cancer [ 31 ]. Recently, Dong D et al found UNC5D as a putative metastatic suppressor gene that is commonly downregulated by hypermethylation in PCa [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Adam23 has been demonstrated to suppress cancer cell metastasis through the interaction with integrins [ 26 ]. Furthermore, such tumor suppressor role has also been demonstrated for Unc5d [ 27 ]. Again, these effects were also supported by the pathway analysis linking miRNA-26b for example to pancreatic cancer and proteoglycans and other cancer related pathways.…”
Section: Discussionmentioning
confidence: 99%